Arthroscopic Treatment of a Low-Velocity Gunshot Injury to a Primary Total Hip Arthroplasty: A Case Report. Issue 1 (January 2019) - Fournier, Matthew N.; Rider, Carson M.; Olinger, Catherine R.; Dabov, Gregory D.; Mihalko, William M.; Mihalko, Marc J.
Abstract : Case: An immunosuppressed 51-year-old man sustained a ballistic injury about the site of a primary total hip arthroplasty, which had been performed for osteonecrosis of the femoral head 2 years earlier. He was treated with arthroscopic debridement and irrigation, inspection of the implants, and removal of foreign bodies. Conclusion: Ballistic injury to a hip arthroplasty site with retained foreign bodies is an unusual injury. Hip arthroscopy may represent a minimally invasive treatment option for implant inspection, joint debridement, and removal of intra-articular fragments while minimizing the risk of soft-tissue complications.